Doing Qualitative Research in Politics Integrating Theory Building and Policy Relevance (Springer International Publishing, 2018)
This volume offers unique perspectives on how to engage in methods of inquiry in Political Science. Applying the debate in the field over the validity of qualitative methods, the authors illustrate how various methodological approaches are both rigorous and empirically rich. Each of the chapters consists of a particular methodological approach that offers useful insight into pressing political problems important for policy and for theory building. Drawing upon both positivist and interpretive approaches, the chapters illustrate how to engage in qualitative research involving case studies, content analysis and ethnography, each outlining the "doing" part of research. The volume is theoretically, thematically and geographically diverse, important for students and scholars across the field. Angela Kachuyevski is Associate Professor of Political Science at Arcadia University, USA. Lisa M. Samuel is Academic Director and Clinical Assistant Professor at New York University's School of Professional Studies Division of Applied Undergraduate Studies, USA.